Visual Imagery in the Novel Kun Fakayun and Dan, Dialah Dia by Andi Bombang - Mubarok, Ahmad; Teguh Supriyanto; Mukh Doyin (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Two novels by Adi Bombang titled Kun Fayakun and Dan, Dialah Dia are very strong in telling stories with visual imagery. The problem of how the author Andi Bombang presents visual imagery in his two novels will be discussed in this study. The study of imagery in novels will provide enrichment for the training of techniques for building novel language. The approach used in this study is a stylistic approach using Leech's theory. The data of this study is the use of majas in two religious novels Kun Fayakun and Dan, Dialah Dia is the dominant one to present visual imagery. The results of the study show that the visual imagery in these two novels is present in the form of personification and hyperbole. The function of imagery in these two novels is not only to beautify the language, but also to strengthen the themes, create an atmosphere, and reveal the conflicts that exist in the story. The meaning of imagery in these two novels is also closely related to the moral message and life values that the author wants to convey. This study found that the use of visual imagery in both novels by Adi Bombang is very effective in depicting the character's mood, reinforcing major themes such as life and spirituality, and revealing inner conflicts in the narrative. In addition, the figurative language techniques used, such as personification and hyperbole, not only beautify the language but also provide emotional depth to the story. This research provides benefits for society, and the development of science, especially readers and literary reviewers, in understanding the power of language in depicting emotional and spiritual realities through visual imagery. In terms of scientific development, this study enriches the discourse of stylistic theory, especially in understanding how visual imagery can be applied in literature to enrich the reader's experience and deepen understanding of universal life themes.